The Effect Of Interval Training On Increasing Vo2max In 1500 M Running Athletes At Semarak Athletic Center Club And Education & Guidance Club In Bengkulu City - Putri, Yevi Melinda; Banat , Azizatul; Personi , Megi (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of interval training on increasing VO2max of 1500-meter sprint athletes at the Semarak Athletic Center club and the Didik & Guidance club. The study is an experimental and control study with a one-group pretest and posttest design. The population of this study were 1500-meter sprint athletes at the Semarak Athletic Center and Didik & Guidance in Bengkulu City. The sample of this study was athletes aged 16-21 years, totaling 30 athletes consisting of 15 athletes from the Semarak Athletic Center club and 15 athletes from the Didik & Guidance club. The sampling technique in this study used a purposive sampling technique. The data collection technique in this study used a test. The instrument used in this study was the Balke test. The data analysis technique used the before-after t-test. The results of the two-tailed t-test showed that there was a significant difference between the two groups of t-values ​​> t-table (3.426 > 2.048) at a significance level of 5% (a = 0.05). So it is concluded that there is a significant effect of the interval training method on the VO2 max level in the experimental group. The hypothesis proposed in this study is proven to have an effect.